Integer solutions for a vector implicit linear difference equation in ZN - Gefter, S.L.; Goncharuk, А.B.; Piven, А.L. (Reports of the National Academy of Sciences of Ukraine, 2018)
A criterion of the existence and the uniqueness for an integer solution of the implicit linear difference equation Axn+1+Bxn=fn, where A and B are matrices with integer entries, is proved. Sufficient conditions of the uniqueness for an integer solution of this equation are obtained.